2022
DOI: 10.1002/adfm.202209023
|View full text |Cite
|
Sign up to set email alerts
|

Toward Unifying the Mechanistic Concepts in Electrochemical CO2 Reduction from an Integrated Material Design and Catalytic Perspective

Abstract: Electrocatalytic CO2 reduction (eCO2RR) is one of the avenues with most potential toward achieving sustainable energy economy and global climate change targets by harvesting renewable energy into value‐added fuels and chemicals. From an industrial standpoint, eCO2RR provides specific advantages over thermochemical and photochemical pathways in terms of much broader product scope, high product specificity, and easy adaptability to the renewable electricity infrastructure. However, unlike water electrolyzers, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 534 publications
0
34
0
Order By: Relevance
“…An electrochemical setup was constructed under a confocal microscope for in situ characterization of an O 2 gradient, when using O 2 -sensitive microbes for the production of biofertilizer (Figure h) . Different operando techniques for mechanistic investigations of CO2RR have been systematically reviewed recently . For example, in situ differential electrochemical mass spectrometry (DEMS), commonly used to detect molecular intermediates (Figure i), can be further adopted to clarify extracellular intermediates of electricity-driven microbial metabolism.…”
Section: Characterization Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…An electrochemical setup was constructed under a confocal microscope for in situ characterization of an O 2 gradient, when using O 2 -sensitive microbes for the production of biofertilizer (Figure h) . Different operando techniques for mechanistic investigations of CO2RR have been systematically reviewed recently . For example, in situ differential electrochemical mass spectrometry (DEMS), commonly used to detect molecular intermediates (Figure i), can be further adopted to clarify extracellular intermediates of electricity-driven microbial metabolism.…”
Section: Characterization Toolsmentioning
confidence: 99%
“…136 Different operando techniques for mechanistic investigations of CO2RR have been systematically reviewed recently. 163 For example, in situ differential electrochemical mass spectrometry (DEMS), commonly used to detect molecular intermediates (Figure 7i), 164 can be further adopted to clarify extracellular intermediates of electricity-driven microbial metabolism.…”
Section: Characterization Toolsmentioning
confidence: 99%
“…For example, alloying Au with Cu not only stabilizes Cu but also reduces the overpotential required for CO 2 reduction. In addition to the excess potential, the selectivity of the catalysts during CO 2 reduction must be considered since multiple couplings between protons and electrons lead to many possible reaction products ( Bagchi et al, 2022 ). Yang’s group showed that Au–Cu alloy nanospheres are a highly potential catalyst for CO 2 reduction ( Kim et al, 2014 ).…”
Section: Applicationsmentioning
confidence: 99%
“…The development of non-precious-metal DACs makes sense for CO 2 electrolysis (cathodic compartment), although a precious-metal (e.g., Pt) electrode is often still used for the anodic compartment (i.e., oxidation of water). Furthermore, it has been demonstrated that an electrode with an area of >5 cm 2 required for larger-scale electrolysis of CO 2 could cause severe heat production at a high current density . Along this line, the design of electrocatalysts for CO 2 electrolysis using a low overpotential would be encouraging toward saving energy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Furthermore, it has been demonstrated that an electrode with an area of >5 cm 2 required for larger-scale electrolysis of CO 2 could cause severe heat production at a high current density. 142 Along this line, the design of electrocatalysts for CO 2 electrolysis using a low overpotential would be encouraging toward saving energy. Because the development of GDEs is appealing for mass production processes, upgrading the technology of electrolyzers will be inevitable.…”
Section: Conclusion and Perspectivementioning
confidence: 99%